Frames We Can Believe In: Official Framing and Ideology in the CCP's Quest for Legitimacy - Maria Bondes; Sandra Heep (German Institute of Global and Area Studies (GIGA), 2012)
In the debate on authoritarian resilience, the importance of persuasion to regime legitimacy has been widely acknowledged, yet a conceptual framework explaining the role of persuasion is still lacking. Against this backdrop, we argue that the framing perspective (Benford and Snow 2000) provides a useful basis for such a framework. Drawing on Beetham's (1991) model of legitimacy, we contend that the ruling elites in authoritarian regimes propagate official frames in a continuous effort to reproduce the belief of the populace in the elites' leadership qualities and their determination to serve the common interest. In the empirical part of our paper we look at the case of China, where the Chinese Communist Party (CCP) has in recent years reemphasized persuasion as a means of reproducing legitimacy. We then apply our theory in an analysis of the conceptual shifts in the CCP's frames and ideology, as propagated under its secretary general, Hu Jintao.
Keywords: 300; Kommunistische Partei; Legitimität; Kommunismus; Meinung; China